2023
DOI: 10.3390/f14071416
|View full text |Cite
|
Sign up to set email alerts
|

Developing Growth and Harvest Prediction Models for Mixed Coniferous and Broad-Leaved Forests at Different Ages

Abstract: In order to clarify the combined impact of tree species composition, site quality, and stand age on the growth and harvest of mixed forests, the prediction models of average DBH and stand volume for mixed forests were established, respectively. The interval period and tree species composition coefficient (TSCC) were considered as independent variables. These models were then optimized by using the particle swarm optimization algorithm for reparameterization and evaluating their applicability. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Most stand-level growth and yield models are used for pure forests, using age to predict the average DBH (diameter at breast height), average height, and volume of the stand. Many studies have shown that stand height increases with the improvement in the site quality, while the average DBH and stocking volume are closely related to the site quality and stand density [21][22][23]. Generally, the average DBH and stand volume also increase with high site quality.…”
Section: Introductionmentioning
confidence: 99%
“…Most stand-level growth and yield models are used for pure forests, using age to predict the average DBH (diameter at breast height), average height, and volume of the stand. Many studies have shown that stand height increases with the improvement in the site quality, while the average DBH and stocking volume are closely related to the site quality and stand density [21][22][23]. Generally, the average DBH and stand volume also increase with high site quality.…”
Section: Introductionmentioning
confidence: 99%